MANAJEMEN STRATEGIK BISNIS PT GOJEK INDONESIA - Melvin L; Febriani F.W; Roby Tan; Mashita Ayuni (Universitas Veteran Bangun Nusantara, 2023)
Basically PT Gojek Indonesia is a company engaged in transportation services that offers various types of services that can connect Gojek partners with customers. Gojek has been operating since 2010, but at that time its services were still limited to online motorcycle taxis. However, as time goes by and the business strategy implemented, Gojek is growing rapidly to achieve a turnover of IDR 29.8 trillion in 2022. Gojek services are now much more varied, not only online motorcycle taxi services but also providing Gocar, Gosend services. , Gofood, Gomart, GoBox, Goclean, GoMassage, GoTix and so on. The business strategic management implemented by Gojek is by utilizing digital media, such as social media, paid advertisements, as well as YouTube and Google content to market and promote its business. In this case, Gojek carries out its promotions by placing paid advertisements on Youtube, making tick-tock, or by making reels on Instagram with interesting animated videos to disseminate and popularize Gojek products to the wider community. This study aims to analyze the application of business strategic management at PT Gojek Indonesia. This research has a qualitative approach, by obtaining data through case studies and literature review of supporting data and information about PT Gojek Indonesia. The results of the study show that PT Gojek Indonesia implements an effective business strategic management to be able to achieve its success in the Indonesian service industry.